International Environmental Law from a Central European Perspective - Raisz, Anikó (International Law From A Central European Perspective, 2022)
International Environmental Law is relevant one way or another for every state as a field where innovative solutions may sculpt the future of international law. Globally connected through climate, the never changing quantity of waters on Earth, or the potential devastating effects of certain transboundary pollutions, states regularly face international environmental challenges. It is even more true for Central European states whose geographical, historical, and cultural proximity explains why this region faces challenges that only partly correspond to the general European trends. The chapter reflects briefly on the economic and social heritage of the region as a possible reason for the particularities of the countries within the region before turning to certain general questions of international environmental law. While presenting some key features of the evolution of international environmental law, we draw attention to issues and achievements relevant for Central European states, in particular in relation to sovereignty and demographic questions. Apart from the main features of international treaties in the field of international environmental law, the chapter refers to the Central European attitude toward IEL treaties. Finally, international environmental adjudication is treated in general, highlighting the main opportunities and possible shortcomings of this field.KEYWORDS: international environmental law, Central Europe, international environmental treaties, international environmental adjudication, evolution of international environmental law